Safety and anti-ulcerogenic activity of a novel polyphenol-rich extract of clove buds (Syzygium aromaticum L). Issue 3 (21st January 2015) - Issac, Abin; Gopakumar, G.; Kuttan, Ramadasan; Maliakel, Balu; Krishnakumar, I. M.
Abstract : Preparation of polyphenol-rich extract of Clove buds [ Syzygium aromaticum ] and its effect on gastric ulcer and inflammation. Abstract : Despite the various reports on the pharmacology of Clove bud [ Syzygium aromaticum ]-derived essential oil and its major component eugenol, systematic information on the bioactivity of clove polyphenols is very limited. Clove buds being one of the richest sources of dietary polyphenols with many traditional medicinal uses, the present contribution attempted to derive their standardized polyphenol-rich extracts as a water soluble free flowing powder (Clovinol) suitable for functional food applications, without the issues of its characteristic pungency and aroma. The extract was characterized by electrospray ionization-time of flight mass spectrometry (ESI-TOF-MS), and investigated for in vivo antioxidant, anti-inflammatory and anti-ulcerogenic activities. Clovinol showed significant antioxidant and anti-inflammatory effects as measured by cellular antioxidant levels, and the ability to inhibit carrageenan-induced paw swelling in mice. Further investigations revealed its significant anti-ulcerogenic activity (>97% inhibition of ethanol-induced stomach ulcers in Wistar rats when orally administered at 100 mg per kg b.w.) and up regulation of in vivo antioxidants such as superoxide dismutase (SOD), glutathione (GSH), and catalase (CAT). Clovinol also reduced the extent of lipid peroxidation among ulcer induced rats, indicating its usefulness in ameliorating oxidative stress and improving gastrointestinal health, especially upon chronic alcohol consumption. The extract was also shown to be safe and suitable for further investigations and development upon acute toxicity studies at 5 g per kg body weight and 28 days of repeated dose toxicity studies at 2.5 g per kg b.w.